DEVELOPING ENGLISH DIGITAL BOOK AS LEARNING MEDIA FOR XI GRADE STUDENTS - Ma'arif, Iin Baroroh; Sunniyah, Intifadzah (JoEMS (Journal of Education and Management Studies), 2021)
This research aims at developing Digital English Book as English learning media for XI grade students of Senior High School. This learning media consist of some materials which is appropriate to be studied for students. All materials in this media is based on senior high school syllabus of curriculum K13. The research method used is Research and Development. This development used ADDIE model which have several steps, those are; 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. The media validation result got 86 score it was in “very good” category, and the material validation got 88 score it was in “very good” category. The students’s responses of try out result 94 was in “very good category”. By having those result, this Digital English Book is feasible to be used as a learning media for XI grade students. Furthermore this research can be used as reference to other researcher in developing English learning media in different level of students. Key words: Digital English Book, English skill, Senior High School Students